Patterns and associations of smoking and electronic cigarette use among survivors of tobacco related and non-tobacco related cancers: A nationally representative cross-sectional analysis. (June 2022) - Bjurlin, Marc A.; Basak, Ramsankar; Zambrano, Ibardo; Schatz, Daniel; El Shahawy, Omar; Sherman, Scott; Matulewicz, Richard S.
Highlights: Survivors of tobacco-related cancers have a higher prevalence of current cigarette smoking, e-cigarette, and dual use compared to survivors of non-tobacco related cancers. There was a sequential increase in cigarette use during each subsequent year from the time of a new cancer diagnosis. There remains the need for long term tobacco cessation support among newly diagnosed adults with cancer. Abstract: Background: Tobacco-use among cancer survivors leads to preventable morbidity, mortality, and increased healthcare costs. We sought to explore the prevalence of smoking and e-cigarette use among survivors of tobacco and non-tobacco related cancers. Methods: A cross-sectional analysis was conducted using the 2015–2018 National Health Interview Survey. Our primary outcome was the prevalence of current cigarette smoking or e-cigarette use among adults with self-reported history of tobacco related or non-tobacco related cancer. Logistic regression analysis was to assess the association of reported cancer type with cigarette smoking or e-cigarette use. Secondary outcomes included yearly trends and dual use. Results: A total of 12, 984 respondents reported a history of cancer, representing a weighted estimate of 5, 060, 059 individuals with a history of tobacco-related malignancy and 17, 583, 788 with a history of a tobacco and non-tobacco related cancer, respectively. Survivors of tobacco-related cancers had a significantly higher prevalence of current cigarette use (18.2 % vs 9.7 %, P < 0.0001), e-cigarette use (2.7 % vs 1.6 %, P < 0.0001) and similar rates of dual use. The prevalence of cigarette smoking among all survivors increased as time increased from the year of diagnosis up to 2 years post-diagnosis ( P = 0.047). Odds of reporting current cigarette smoking use was higher for survivors of tobacco-related cancers, adjusted for sociodemographic factors (OR1.69, 95 % CI 1.44−1.99). Conclusions: Survivors of tobacco-related cancers have a higher prevalence of current cigarette smoking and e-cigarette use compared to survivors of non-tobacco related cancers. There was a sequential increase in the prevalence of cigarette use during each subsequent year from the time of a new cancer diagnosis, underscoring the need for long term tobacco cessation support among newly diagnosed adults with cancer.